Assessing the household saving behavior of urban and rural households in Pakistan: Evidence from PSLM/HIES 2018-19 - Aslam, Maria; Saleem, Sehar; Mukhtar, Warda; Firdous, Rehana (Pakistan Journal of Humanities and Social Sciences, 2022)
The purpose of this article is to examine household saving behavior in urban and rural areas of Pakistan. The study obtained microdata from the Household Integrated Economic Survey (HIES) 2018-19 and Pakistan Social Living Standards Measurements Survey (PSLM) 2018-19 conducted by the Pakistan Bureau of Statistics (PBS). A nationally representative sample of 5499 households is selected, 3155 from rural areas and 2344 from urban areas by using systematic sampling. The impact of socioeconomic and demographic characteristics on household saving behavior is investigated by applying a multiple linear regression model through Ordinary Least Squares (OLS) estimation method. A strong relationship between household saving behavior and socioeconomic and demographic characteristics is observed. Income has a positive impact on household savings, but age, dependency ratio, and family size have a negative effect. Furthermore, it is found that as the household income rises, their savings rise as well. Although, people residing in rural areas tend to save more amount contrary to urban households. However, saving rates of household with large families exhibited a decline in saving. Government should introduce new saving schemes in banks and reduce non-development expenditures for productive plans. It will provide motivation for domestic saving and an upsurge in employment opportunities.